Photocurable hybrid polysiloxane resin and preparation method thereof
The hybrid polysiloxane resin formed by polycondensation reaction in anhydrous solvent system solves the problems of complex nanoparticle preparation process and low resin transparency, and achieves resin preparation with high refractive index and transparency, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411968761.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the nanoparticle preparation process is complex, and the dispersion in the matrix resin is uneven, resulting in a decrease in the transparency of the material, and the resin has a low light refractive index or a darker color.
By polycondensing the alkoxy zirconium monomer and the alkoxy silane monomer with the silicone glycol monomer in anhydrous solvent system, a hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure and the side chain contains photocurable functional groups.
The refractive index of the resin is regulated between 1.5-1.61, maintaining high transparency and refractive index, and solving the problems of complex process and low material transparency in traditional methods.
Smart Images

Figure CN119751876A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic-inorganic hybrid materials and photocurable silicone resins, and in particular to a photocurable hybrid polysiloxane resin and a preparation method thereof. Background Art
[0002] Light Emitting Diode, or LED for short, is a new type of light source with low energy consumption, high light intensity and light efficiency, and is green and environmentally friendly. It is widely used in commercial lighting, large-area graphic displays, and backlight sources for electronic and electrical equipment such as mobile phones and LCD TVs. As an important component of LED devices, packaging materials directly affect their light output efficiency and service life. In particular, silicone packaging materials have become a popular product among LED packaging materials due to their superior physical and chemical properties. The refractive index of commonly used silicone resins is currently around 1.4 to 1.5. Based on this, in order to reduce the total reflection phenomenon inside LED devices and improve light output efficiency, it is necessary to increase the refractive index of silicone resins.
[0003] The method to increase the refractive index of silicone resin is usually to introduce atoms or groups with high molar refractive index into the polymer molecular structure, such as sulfur atoms, halogens, aromatic rings or condensed ring structures, or to add inorganic nanoparticles with high refractive index into the polymer, such as TiO2, ZrO2, ZnS, etc.
[0004] In the prior art with patent application number CN201010604815.2, a silicone resin containing both thienyl and phenyl groups is synthesized, and then the silicone resin is heat-cured with a hydrogen-containing phenyl silicone resin. The obtained organosilicon cured product has a light refractive index of 1.52, a hardness of more than 40D, a tensile strength of> 8MPa, and no cracking occurs under a cycle of -50°C to 100°C. In the prior art with patent application number US20070221939, nano-TiO2 particles are prepared using butyl titanate, and coated with a magnesium compound to form a core-shell structure, and the surface of the core-shell nano-particles is modified. The modified nano-TiO2 is added to the organosilicon resin to prepare an LED nano-composite packaging material, whose refractive index is about 1.7, which increases the light extraction efficiency of the LED. However, the above preparation method is relatively complicated and is not suitable for large-scale production. In addition, the nano-particles are not easy to be evenly dispersed in the matrix resin, and are prone to agglomeration, which reduces the transparency of the material.
[0005] In the prior art with patent application number CN201310163123.2, Ti atoms are introduced into the silicone chain segments by chemical bonding, which significantly improves the refractive index of the silicone resin to as high as 1.62. At the same time, the silicone resin maintains good transparency, but the resin is dark in color and has strong absorption in the ultraviolet region, which affects its light-emitting effect. Summary of the invention
[0006] In order to solve the problems of complicated preparation process of nanoparticles in the prior art, uneven dispersion in the matrix resin, thereby reducing the transparency of the material, and the problem that the resin prepared by the prior art has a low refractive index or dark color, the purpose of the present invention is to provide a photocurable hybrid polysiloxane resin and a preparation method thereof.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] In one aspect, the present invention provides a method for preparing a photocurable hybrid polysiloxane resin, comprising the following steps:
[0009] Under the protection of an inert atmosphere, in an anhydrous solvent system, an alkoxy zirconium monomer and an alkoxy silane monomer are subjected to a polycondensation reaction with a silicon glycol monomer in the presence of a catalyst, and the temperature of the polycondensation reaction is 80-110° C. After the reaction is completed, a hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure and a photocurable functional group in the side chain is prepared; the photocurable structural unit is a double bond and / or a mercapto group; the alkoxy silane monomer is a trifunctional or difunctional alkoxy silane monomer containing a photocurable functional group; and the silicon glycol monomer is a phenyl-containing silicon glycol monomer.
[0010] The present invention mainly obtains a hybrid polysiloxane resin having Si-O-Si and Zr-O-Si structural units in the main chain structure and a photocurable functional group in the side chain by co-condensing the alkoxy group in the alkoxy zirconium monomer and the alkoxy silane monomer with Si-OH in the silicon diol monomer. The present invention helps to improve the refractive index of the resin and maintain good light transmittance by introducing zirconium elements and phenyl groups, and solves the problems of the complicated preparation process of nanoparticles in the prior art, easy uneven dispersion in the matrix resin, thereby reducing the transparency of the material, and the problem that the resin prepared by the prior art has a low light refractive index or a darker color.
[0011] Preferably, the trifunctional alkoxysilane monomer is one of vinyl trimethoxysilane, vinyl triethoxysilane, allyl trimethoxysilane, allyl triethoxysilane, mercaptopropyl trimethoxysilane and mercaptopropyl triethoxysilane. The difunctional alkoxysilane monomer is one of methyl vinyl dimethoxysilane, methyl vinyl diethoxysilane, methyl allyl dimethoxysilane, methyl allyl diethoxysilane, methyl mercaptopropyl dimethoxysilane and methyl mercaptopropyl diethoxysilane.
[0012] Preferably, the zirconium alkoxide monomer is one of zirconium ethoxide, zirconium n-propoxide, zirconium isopropoxide, zirconium tert-butoxide and zirconium n-butoxide.
[0013] Preferably, the silicon diol monomer is at least one of diphenylsilanediol, 1,4-bis(dimethylhydroxysilyl)benzene, and 4,4'-bis(dimethylhydroxysilyl)diphenyl ether.
[0014] Preferably, the ratio of the molar amount of the zirconium alkoxy monomer to the total molar amount of the alkoxysilane monomer and the silanol monomer is 0.01 to 0.4:1; preferably 0.03 to 0.3:1; the ratio of the total molar amount of the alkoxy groups of the zirconium alkoxy monomer and the alkoxysilane monomer to the molar amount of the hydroxyl group of the silicon glycol monomer is 1 to 2:1; preferably 1 to 1.7:1.
[0015] The present invention helps to regulate the content of photocurable C=C double bonds and / or mercapto groups by adjusting the amount of alkoxysilane monomer added, thereby helping to regulate the performance of the material prepared from the hybrid polysiloxane resin.
[0016] Preferably, the molar amount of the catalyst accounts for 0.1% to 0.7% of the total molar amount of the alkoxy zirconium monomer, the alkoxy silane monomer and the silicon glycol monomer. It is found through experiments that when the catalyst is within this range, a photocurable hybrid polysiloxane resin can be prepared.
[0017] Preferably, the total mass ratio of the zirconium alkoxy monomer, the silane alkoxy monomer and the silicon glycol monomer to the mass ratio of the solvent is 1:1-6.
[0018] Preferably, the catalyst is at least one of potassium hydroxide, sodium hydroxide, barium hydroxide monohydrate and dibutyltin dilaurate.
[0019] Preferably, the solvent is at least one of toluene, xylene, n-hexane, n-heptane and cyclohexane. The present invention does not limit the selected solvent to xylene. The solvent used in the present invention can be selected according to actual needs.
[0020] Preferably, the polycondensation reaction time is 4 h to 24 h.
[0021] The present invention adopts a de-low polycondensation process and micron filtration technology to remove small molecular substances generated during the reaction and impurities such as catalysts remaining in the system after the reaction is completed, and then vacuum removes the remaining low-volatile components in the resin to obtain a viscous and transparent polymer.
[0022] Another aspect of the present invention provides a photocurable hybrid polysiloxane resin. The hybrid polysiloxane resin described in the first aspect can be photocured to prepare a hybrid material.
[0023] Beneficial effects of the present invention:
[0024] 1. The present invention mainly obtains a hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure and photocurable functional groups in the side chain by co-condensation of the alkoxy groups in the alkoxy zirconium monomer and the alkoxy silane monomer and Si-OH in the silicon diol monomer. The present invention helps to improve the refractive index of the resin and maintain good light transmittance by introducing zirconium elements and phenyl groups, and solves the problems of uneven dispersion, easy agglomeration, reduced transparency of the material and complicated preparation process in the prior art of introducing high-refractive nanoparticles into the matrix resin, as well as the problems of low refractive index and dark color of the organic silicone resin prepared by the prior art.
[0025] 2. The refractive index of the photocurable hybrid polysiloxane resin prepared by the method of the present invention is adjustable between 1.5 and 1.61, and has high transparency and refractive index. The preparation method of the present invention has the characteristics of mild reaction conditions, simple process and easy post-treatment, and is suitable for industrial production.
[0026] 3. Compared with traditional silicone resins, the residual Si-OH content in the photocurable hybrid polysiloxane resin prepared by the method of the present invention is low, and the structure of the photocurable hybrid polysiloxane resin prepared by the method of the present invention has Si-O-Si and Zr-O-Si segments, and the side chain has a photoreactive functional group, so it can be used to prepare optical hybrid materials with good photocuring properties. This material has a very broad application prospect in the fields of high-power LED packaging materials and special coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is the infrared spectra of hybrid polysiloxane resins with different zirconium contents.
[0028] Figure 2 is the NMR silicon spectrum of hybrid polysiloxane resin with different zirconium contents.
[0029] Figure 3 : is a graph showing the relationship between the refractive index and zirconium content of hybrid polysiloxane resins with different contents. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0032] In previous studies, the traditional co-hydrolysis condensation process was used to co-hydrolyze and condense silicone monomers and alkoxy zirconium monomers. However, the hydrolysis rates of silicone monomers and alkoxy zirconium monomers did not match, resulting in the prepared silicone resin being opaque and prone to gel or precipitation problems.
[0033] The present invention adopts a stepwise polycondensation reaction, introduces a high molar refractive index benzene ring and a zirconium element by chemical bonding, and prepares a hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure, and a photocurable functional group in the side chain, which is transparent and has a high refractive index. The method of the present invention has the characteristics of simple process, convenient operation, easy post-treatment, and adjustable refractive index and C=C double bond or mercapto content, and solves the problem that the hydrolysis rate of the organic silicon monomer and the alkoxy zirconium monomer in the traditional co-hydrolysis condensation process does not match, resulting in opaque resin and easy generation of gel or precipitation.
[0034] The hybrid polysiloxane resin containing photocurable functional groups prepared by the present invention contains C=C double bonds and / or mercapto groups, and the corresponding hybrid polysiloxane material can be prepared by photocuring the hybrid polysiloxane resin containing C=C double bonds with the hybrid polysiloxane resin containing mercapto groups. The present invention helps to control the content of photocurable C=C double bonds and / or mercapto groups by adjusting the amount of alkoxysilane monomer added, thereby helping to control the performance of the material after photocuring. At the same time, the photocuring reaction has the advantages of energy saving, high efficiency, green environmental protection, etc.
[0035] The technical solution of the present invention is further described below through specific embodiments.
[0036] In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0037] Example 1
[0038] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0039] In a 150mL three-necked flask with a condenser, add 3.96g / 26.7mmol vinyltrimethoxysilane, xylene and 36.6mg / 0.193mmol monohydrated barium hydroxide, and heat to 85°C while stirring. After stirring evenly, slowly drop diphenylsilanediol-xylene solution and tetraethoxyzirconium-xylene solution into the flask at the same time. The amount of diphenylsilanediol added is
[0040] The addition amount of tetraethoxy zirconium was 12.98 g / 60 mmol, and the addition amount of tetraethoxy zirconium was 2.71 g / 10 mmol; after both were added, the reaction continued for 10 hours, and the entire reaction was carried out in a nitrogen atmosphere. The total amount of xylene used in the entire reaction was 50 g.
[0041] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.586 / 25°C.
[0042] Example 2
[0043] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0044] In a 100mL three-necked flask with a condenser, add 1.18g / 7.95mmol vinyltrimethoxysilane, xylene and 15mg / 0.087mmol monohydrated barium hydroxide, and heat to 100°C while stirring. After stirring evenly, slowly drop 1,4-bis(dimethylhydroxysilyl)benzene-xylene solution and tetraethoxyzirconium-xylene solution into the flask at the same time, wherein the amount of 1,4-bis(dimethylhydroxysilyl)benzene added is 3g / 13.25mmol, and the amount of tetraethoxyzirconium added is 1.438g / 5.3mmol; after both are added, the reaction continues for 15h, and the entire reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the entire reaction is 15g.
[0045] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.515 / 25°C.
[0046] Example 3
[0047] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0048] Add 1.48g / 10mmol vinyltrimethoxysilane, xylene and 31mg / 0.181mmol monohydrated barium hydroxide to a 100mL three-necked flask with a condenser, and heat to 100°C while stirring. After stirring evenly, slowly drop 4,4'-bis(dimethylhydroxysilyl)diphenyl ether-xylene solution and tetraethoxyzirconium-xylene solution into the flask at the same time, wherein the amount of 4,4'-bis(dimethylhydroxysilyl)diphenyl ether added is 4.78g / 15mmol, and the amount of tetraethoxyzirconium added is 0.678g / 2.5mmol; after both are added, the reaction continues for 20h, and the entire reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the entire reaction is 30g.
[0049] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.545 / 25°C.
[0050] Example 4
[0051] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0052] In a 150mL three-necked flask with a condenser, add 2.43g / 15mmol allyltrimethoxysilane, xylene and 49mg / 0.286mmol monohydrated barium hydroxide, stir and heat to 100°C, after stirring evenly, slowly drop diphenylsilanediol-xylene solution and zirconium isopropoxide-xylene solution into the flask at the same time, wherein the amount of diphenylsilanediol added is 7g / 32.5mmol, and the amount of zirconium isopropoxide added is 1.638g / 5mmol; after both are added, the reaction continues for 10h, and the whole reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the whole reaction is 50g.
[0053] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.59 / 25°C.
[0054] Example 5
[0055] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0056] In a 150mL three-necked flask with a condenser, add 3.93g / 20mmol mercaptopropyl trimethoxysilane, xylene and 21.27mg / 0.124mmol monohydrated barium hydroxide, stir and heat to 85°C, after stirring evenly, slowly drop diphenylsilanediol-xylene solution and tetraethoxy zirconium-xylene solution into the flask at the same time, wherein the amount of diphenylsilanediol added is 6.49g / 30mmol, and the amount of tetraethoxy zirconium added is 2.17g / 8mmol; after both are added, the reaction continues for 10h, and the whole reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the whole reaction is 50g.
[0057] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.58 / 25°C.
[0058] Example 6
[0059] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0060] In a 100mL three-necked flask with a condenser, add 1.97g / 10mmol mercaptopropyltrimethoxysilane, xylene and 31mg / 0.181mmol monohydrated barium hydroxide, and heat to 110°C while stirring. After stirring evenly, slowly drop 4,4'-bis(dimethylhydroxysilyl)diphenyl ether-xylene solution and zirconium isopropoxide-xylene solution into the flask at the same time, wherein the amount of 4,4'-bis(dimethylhydroxysilyl)diphenyl ether added is 6.37g / 20mmol, and the amount of zirconium isopropoxide added is 0.819g / 2.5mmol; after both are added, the reaction continues for 20h, and the entire reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the entire reaction is 30g.
[0061] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.541 / 25°C.
[0062] Example 7
[0063] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0064] In a three-necked flask with a condenser of 100 mL, add 2.645 g / 20 mmol methylvinyldimethoxysilane, xylene and 55 mg / 0.321 mmol monohydrated barium hydroxide, stir and heat to 85 ° C, after stirring evenly, slowly drop diphenylsilanediol-xylene solution and tetraethoxyzirconium-xylene solution into the flask at the same time, wherein the amount of diphenylsilanediol added is 6.49 g / 30 mmol, and the amount of tetraethoxyzirconium added is 1.36 g / 5 mmol; after both are added, the reaction continues for 16 hours, and the whole reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the whole reaction is 40 g.
[0065] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.588 / 25°C.
[0066] Example 8
[0067] A method for preparing a photocurable hybrid polysiloxane resin comprises the following steps:
[0068] In a 100mL three-necked flask with a condenser, add 3.61g / 20mmol methylmercaptopropyldimethoxysilane, 40g xylene and 55mg / 0.32mmol monohydrated barium hydroxide, and heat to 100°C while stirring. After stirring evenly, slowly drop 1,4-bis(dimethylhydroxysilyl)benzene-xylene solution and zirconium isopropoxide-xylene solution into the flask at the same time, wherein the amount of 1,4-bis(dimethylhydroxysilyl)benzene added is 5.66g / 25mmol, and the amount of zirconium isopropoxide added is 1.309g / 4mmol; after both are added, the reaction continues for 15h, and the entire reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the entire reaction is 40g.
[0069] At the end of the reaction, a water separation device is used to separate the by-products and promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin. The refractive index is 1.503 / 25°C.
[0070] In the above embodiment of the present invention, the alkoxy groups in the alkoxy zirconium alkoxide monomer and the alkoxysilane monomer co-condense with the Si-OH in the silicon diol monomer to obtain a colorless, transparent, high-refractive-index hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure and a side group containing a photocurable structural unit. In the above embodiment of the present invention, the introduction of zirconium elements and phenyl groups helps to adjust the refractive index of the resin, and the refractive index is above 1.5.
[0071] In order to explore the effect of different zirconium addition amounts on the prepared photocurable hybrid polysiloxane resin, the following experiment was conducted.
[0072] Example 9
[0073] A method for preparing a photocurable hybrid polysiloxane resin, which differs from Example 1 in that the amount of tetraethoxy zirconium added is 15 mmol. The specific method comprises the following steps:
[0074] In a 150mL three-necked flask with a condenser, add 2.965g / 20mmol vinyltrimethoxysilane, 50g xylene and 36mg / 0.19mmol monohydrated barium hydroxide, stir and heat to 85°C, after stirring evenly, slowly drop diphenylsilanediol-xylene solution and tetraethoxy zirconium-xylene solution into the flask at the same time, wherein the amount of diphenylsilanediol added is 12.98g / 60mmol, and the amount of tetraethoxy zirconium added is 4.065g / 15mmol; after both are added, the reaction continues for 10h, and the whole reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the whole reaction is 50g.
[0075] At the end of the reaction, a water separation device is used to separate the by-products to promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin.
[0076] Example 10
[0077] A method for preparing a photocurable hybrid polysiloxane resin, which differs from Example 1 in that the amount of tetraethoxy zirconium added is 20 mmol. The specific method comprises the following steps:
[0078] In a 150mL three-necked flask with a condenser, add 1.986g / 13.4mmol vinyltrimethoxysilane, 50g xylene and 35.4mg / 0.187mmol monohydrated barium hydroxide, stir and heat to 85°C, after stirring evenly, slowly drop diphenylsilanediol-xylene solution and tetraethoxy zirconium-xylene solution into the flask at the same time, wherein the amount of diphenylsilanediol added is 12.98g / 60mmol, and the amount of tetraethoxy zirconium added is 5.42g / 20mmol; after both are added, the reaction continues for 10h, and the whole reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the whole reaction is 50g.
[0079] At the end of the reaction, a water separation device is used to separate the by-products to promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin.
[0080] Comparative Example 1
[0081] A method for preparing a photocurable hybrid polysiloxane resin, which differs from Example 1 in that tetraethoxy zirconium is not added. The specific method comprises the following steps:
[0082] In a 100mL three-necked flask with a condenser, add 5.93g / 40mmol vinyltrimethoxysilane, 50g xylene and 38mg / 0.2mmol monohydrated barium hydroxide, stir and heat to 80°C, after stirring evenly, slowly drop diphenylsilanediol-xylene solution into the flask at the same time, wherein the amount of diphenylsilanediol added is 12.98g / 60mmol; after all are added, the reaction continues for 10h, and the whole reaction is carried out in a nitrogen atmosphere. The total amount of xylene used in the whole reaction is 50g.
[0083] At the end of the reaction, a water separation device is used to separate the by-products to promote the polycondensation reaction. After the reaction is completed, the reactants are cooled to room temperature and filtered using a micron-level oily filter membrane to remove impurities such as residual catalysts in the system. The filtrate is vacuum-dried to remove volatiles to obtain a transparent resin, which is a hybrid polysiloxane resin.
[0084] The hybrid polysiloxane resin prepared in Example 1 of the present invention is recorded as Zr-10; the hybrid polysiloxane resin prepared in Example 9 is recorded as Zr-15; the hybrid polysiloxane resin prepared in Example 10 is recorded as Zr-20; and the hybrid polysiloxane resin prepared in Comparative Example 1 is recorded as Zr-0. The samples Zr-10, Zr-15, Zr-20 and Zr-0 were subjected to infrared spectroscopy analysis, nuclear magnetic resonance silicon spectroscopy analysis and refractive index analysis, respectively. The results are as follows: Figure 1 to Figure 3 shown.
[0085] Figure 1 It is the infrared spectra of hybrid polysiloxane resins with different zirconium contents.
[0086] from Figure 1 It can be seen from the infrared spectrum that with the gradual increase of zirconium content in the hybrid polysiloxane resin, 3413cm -1 The -OH absorption peak at 3070 cm disappeared, indicating that vinyltrimethoxysilane and diphenylsilanediol reacted completely; -1 、3050cm -1 、3024cm -1 The peak at 1965cm is the CH stretching vibration absorption peak on the benzene ring in DSPD; -1 ~1770cm -1 The absorption peak is a unique absorption peak on the two benzene rings connected by Si, which is four consecutive absorption peaks; 1591cm -1 、1408cm -1 、1014cm -1 It is the stretching vibration absorption peak of Si-CH=CH2; 1127cm -1 The peak at 1077cm -1 The broad peak at 964cm is the Si-O-Si stretching vibration absorption peak; -1 A weaker absorption peak appears at the center, which is the characteristic absorption peak of Si-O-Zr. This shows that a condensation reaction does occur between the alkoxy group and the hydroxyl group under the action of the catalyst.
[0087] Figure 2 The NMR silicon spectra of hybrid polysiloxane resins with different zirconium contents are shown in Figure 1. Among them, D1 is δ = -36ppm, representing HO- Si Chemical shift of (Ph)2-OSi; δ = -38 ppm represents HO- Si (Ph)2-OZr chemical shift; D2 is δ = -41ppm ~ -45ppm, representing Si-O- Si Chemical shift of (Ph)2-O-Si; T2 is δ = -72ppm, representing -O-Si(Ph)2-O Si Chemical shift of (OMe)-OSi; T3 is δ = -78 ppm, representing -O-Si(Ph)2-O Si Chemical shift of (-OSi(Ph)2)2, wherein Ph represents phenyl and Me represents methyl.
[0088] Figure 3 : is a graph showing the relationship between the refractive index and zirconium content of hybrid polysiloxane resins with different contents.
[0089] Depend on Figure 3 It can be seen that the zirconium alkoxide content has a great influence on the refractive index of the hybrid polysiloxane resin, and there is an approximately linear relationship between them. As the zirconium alkoxide content increases, the refractive index of the hybrid polysiloxane resin gradually increases. However, the excessive increase in the zirconium alkoxide content will cause the viscosity of the resin system to be very high, and it will appear semi-solid, affecting the later preparation process of the material.
[0090] In summary, the embodiments of the present invention mainly obtain a hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure and photocurable functional groups in the side chain by co-condensation of the alkoxy groups in the alkoxy zirconium monomer and the alkoxy silane monomer with the Si-OH in the silicon diol monomer. The embodiments of the present invention help to improve the refractive index and light transmittance of the resin by introducing zirconium elements and phenyl groups. The refractive index of the hybrid polysiloxane resin prepared by the method of the embodiments of the present invention is adjustable between 1.5 and 1.61, and has a high refractive index and light transmittance. The preparation method of the embodiments of the present invention has readily available raw materials, mild reaction conditions, simple process, strong operability, and is suitable for industrial production.
[0091] Compared with traditional silicone resins, the content of residual Si-OH in the hybrid polysiloxane resin prepared by the method of the embodiment of the present invention is low, and the structure of the hybrid polysiloxane resin prepared by the method of the embodiment of the present invention has Si-O-Si and Zr-O-Si segments, and the side groups have photoreactive functional groups, so it can be used to prepare resin materials with good photocuring properties. And because there is no problem of cracking and shrinkage when preparing thick films, it has very broad application prospects in the fields of high-power LED packaging materials and special coatings.
[0092] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a photocurable hybrid polysiloxane resin, characterized in that: The following steps are involved: Under the protection of an inert atmosphere, in an anhydrous solvent system, alkoxy zirconium monomers, alkoxy silane monomers and silicon diol monomers undergo polycondensation reaction under the action of a catalyst, and the temperature of the polycondensation reaction is 80° C. to 110° C. After the reaction is completed, a hybrid polysiloxane resin containing Si-O-Si and Zr-O-Si structural units in the main chain structure and photocurable structural functional groups in the side chain is prepared; The photocurable functional group is a double bond or a mercapto group; the alkoxysilane monomer is a trifunctional or difunctional alkoxysilane monomer containing a photocurable functional group; and the silicon diol monomer is a silicon diol monomer containing a phenyl group.
2. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The trifunctional alkoxysilane monomer is one of vinyltrimethoxysilane, vinyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, mercaptopropyltrimethoxysilane and mercaptopropyltriethoxysilane; The difunctional alkoxysilane monomer is one of methylvinyldimethoxysilane, methylvinyldiethoxysilane, methylallyldimethoxysilane, methylallyldiethoxysilane, methylmercaptopropyldimethoxysilane and methylmercaptopropyldiethoxysilane.
3. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The zirconium alkoxide monomer is one of zirconium ethoxide, zirconium n-propoxide, zirconium isopropoxide, zirconium tert-butoxide and zirconium n-butoxide.
4. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The silicon diol monomer is at least one of diphenyl silicon diol, 1,4-bis(dimethylhydroxysilyl)benzene and 4,4'-bis(dimethylhydroxysilyl)diphenyl ether.
5. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The ratio of the molar amount of the alkoxy zirconium monomer to the total molar amount of the alkoxy silane monomer and the silanol monomer is 0.01 to 0.4:1; The ratio of the total alkoxy molar amount of the zirconium alkoxide monomer and the alkoxysilane monomer to the hydroxyl molar amount of the silicon diol monomer is 1 to 2:
1.
6. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The molar amount of the catalyst accounts for 0.1% to 0.7% of the total molar amount of the alkoxy zirconium monomer, the alkoxy silane monomer and the silicon glycol monomer.
7. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The mass ratio of the total mass of the alkoxy zirconium monomer, the alkoxy silane monomer and the silicon diol monomer to the mass of the solvent is 1:1-6.
8. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The catalyst is at least one of potassium hydroxide, sodium hydroxide, barium hydroxide monohydrate and dibutyltin dilaurate.
9. The method for preparing a photocurable hybrid polysiloxane resin according to claim 1, characterized in that: The solvent is at least one of toluene, xylene, n-hexane, n-heptane and cyclohexane.
10. A photocurable hybrid polysiloxane resin, characterized in that: The photocurable hybrid polysiloxane resin is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Synthesis method of thienyl phenyl silicon resin for packaging light-emitting diode (LED)
CN102093581A
High refractive index titanium hybrid silicon resin and preparation method thereof
CN103265703A
Optically reliable nanoparticle based nanocomposite HRI encapsulant, photonic waveguiding material and high electric breakdown field strength insulator / encapsulant
US20070221939A1
High-temperature resistant zirconium silicon resin containing zirconium in frame structure and preparation method thereof
CN102675648A
Synthesis method of high-refractive index organic silicon resin
CN103627001A